Molecular characterization of Canna indica L. based on random amplified polymorphic DNA markers (Bangladesh Journal of Plant Taxonomy, 2021)
Random amplified polymorphic DNA (RAPD) markers were employed for characterization, assessment of genetic variation and inferring relationships among six variants of Canna indica L. A total of 198 RAPD bands ranging from 200 bp to 3 kbp were generated by all the six variants. Among them, most of the bands were found to be polymorphic, four band were unique of which two bands (OPA022000 and OPA043000) were observed in the variant 2 (small red) and the other two (OPA013000 and OPA053000) were noticed in the variant 4 (orange), and the remaining bands were found to be monomorphic. The pair-wise genetic distance was determined among the six variants that ranged from 0.1446 to 0.6554. A dendogram was constructed based on the RAPD profiling to infer the relationship among the six variants of C. indica that resulted in two major clusters: the first one contained two variants, viz. variant 1 (local red) and variant 2 (small red), while the second cluster composed of the remaining four variants. The results as revealed from the RAPD analysis were found congruent with those of morphological and anatomical investigation of the species.Bangladesh J. Plant Taxon. 28(1): 75-81, 2021 (June)